Adaptasi Terhadap Perkembangan Teknologi Digital oleh Pedagang Tradisional di Pasar Lama Kota Banjarmasin - Aria Adi Prasojo; Sri Hidayah (Huma: Jurnal Sosiologi, 2023)
Pasar Lama is a traditional market in Banjarmasin City, where the trading system is generally still carried out conventionally, but nowadays the presence of digital technology has had quite a detrimental impact on traders because many people have switched to using digital transactions. This study aims to determine changes in traditional merchants in the use of digital technology. The research method used is a descriptive qualitative approach. Data collection techniques using observation, interviews, and documentation. Setting the time and location of the research from December 2022 to May 2023 in the Old Market of Banjarmasin City. The results showed that there was an adaptation process made by Old Market traders, namely using digital technology introduced by the closest people such as relatives, customers, friends and so on. The addition process is a stage in the use of digital technology by traders at Old Market, at this stage traders can already develop businesses through digital services. The adjustment process is the stage of acceptance of traders from the presence of Digital Technology, At this stage, traders can combine direct in-store services with services via digital media. Discovery and innovation is the process of traders in adapting to changes by applying digital technology to their merchandise. The adaptation of changes made by traders aims to be able to maintain and develop the businesses they have so that they can continue to compete in this day.